The Role of Halal Awareness in Encouraging the Implementation of Halal Certification MSMEs - Citra Meylana Rina Jayanti; Badrika Yelipelle; Shima Fauziah Yeubun (Sean Institute, 2026)
The rapid development of the halal industry has increased the need for micro, small, and medium enterprises (MSMEs) to comply with halal standards through the implementation of halal certification. However, many MSME actors still face challenges in adopting halal certification due to limited understanding and awareness of halal principles in business practices. This study aims to analyze the role of halal awareness in encouraging the implementation of halal certification among MSMEs. The research employs a qualitative approach using secondary data obtained from academic publications, institutional reports, and related documents concerning halal awareness and MSME development. The data were analyzed through qualitative content analysis to identify patterns and conceptual relationships regarding halal awareness and certification adoption. The findings indicate that halal awareness plays a significant role in encouraging MSMEs to implement halal certification, particularly through the interaction of religious commitment, knowledge of halal standards, market demand, and perceived business credibility. MSME actors who possess stronger awareness of halal principles tend to view halal certification not merely as a regulatory requirement but as a strategic instrument to enhance consumer trust, strengthen product credibility, and expand market competitiveness. This study concludes that strengthening halal awareness among MSME actors is a crucial factor in supporting the sustainable implementation of halal certification and the development of a more inclusive halal ecosystem.